Stress management in IT companies in India - Natarajan, Divya dharsana (2014)
For the past few decades there were literatures based on the stress management in IT companies. However, these studies examined about the stress of Information technology professionals working in IT companies and about the stress management programs followed in those IT organizations, very less number of research have been taken place in India when compared to the developed countries like United States and United Kingdom. The main focus of this research is to explore the stress levels of IT professionals in India and its impact on their work and health. For this, the main focus was given to three different designations of Indian IT professionals - senior managers, middle level managers and developers. And this study also mentions the category facing high amount of stress and about the effective ways the organizations uses to handle their employees’ stress. For this study a qualitative research was conducted. Telephonic and email interviews were done for the same. A total of fourteen members were considered for the research, where three from senior managers, six from middle level and five from the developers. The research clearly explains that, the managers face high stress when compared to developers, especially in case of middle level and also it gives information related to various stress management programs followed by IT organizations in India.